Pelatihan Pengolahan Data untuk Analisis Jalur dengan Menggunakan SPSS v.22 pada Mahasiswa Magister Manajemen UNIKI Bireuen - Kamaruddin K; Azhari Azhari; Win Konadi; Rizkan Abqa (Aceh Journal of Community Engagement (AJCE), 2023)
Lecturer service activities in the form of training aim to increase participants' understanding, ability to use path analysis and skills in processing data with the SPSS application program. The training method is divided into the stages of material preparation and selection of participants, implementation by face-to-face interviews and practice, as well as evaluation of training results through discussions and post tests. The results of the activity show an increase in ability, understanding of the application of path analysis and the benefits of knowledge, skills from training and application of data processing results by being able to interpret them to help students complete thesis research analysis as teaching materials. requirements for later completion of the master of management studies